Relationship between muscle coordination and racket mass during forehand drive in tennis - Rogowski, I.; Creveaux, T.; Faucon, A.; Rota, S.; Champley, S.; Guillot, A.; Hautier, C. (European Journal of Applied Physiology, 2009)
This study aimed at investigating the relationship between the trunk and upper limb muscle coordination and mass of the tennis racket during forehand drive. A total of 15 male tennis players performed seven series of ten crosscourt forehand drives, both with their personal racket and six rackets with increased mass ranging from 6 to 16% (step = 2%) of their personal racket mass. The electromyographic (EMG) activity was recorded from nine trunk and upper limb muscles. The onset before impact and EMGrms values of the bursts were individually calculated. Results showed that the ball speed and the muscle activation temporal sequences were similar, whatever the increase in racket mass. Interestingly, in all participants, the activation level of the pectoralis major, latissimus dorsi and biceps brachii decreased when the racket mass increased, while the variations in the anterior deltoid activation level were correlated to the individual personal racket mass. These findings strongly suggest that the study of muscle activity during tennis practice should be considered as a complementary technique to determine a better adequacy of the racket characteristics to those of the player.